The Jesus tradition in Q - Allison, Dale C. 1955- (Trinity Press International, 1997)
A thesis regarding Q's composition precedes chapters on specific texts and events.
Keywords: Jésus-Christ - Paroles; Jesus Christus; Jesus Christ -- Words; Logienquelle; Document Q (Critique biblique); Document Q (critique biblique); Leven van Jezus; Q-bron; Q hypothesis (Synoptics criticism); Traditionsgeschichtliche Forschung; Redaktion